Site selection of wind farms using GIS and multi-criteria decision making method in Wafangdian, China. (15th September 2020) - Xu, Ye; Li, Ye; Zheng, Lijun; Cui, Liang; Li, Sha; Li, Wei; Cai, Yanpeng
Abstract: Site selection is one of the most significant decision making activities for development of wind energy resource. In this study, a novel method integrating Geographic Information System (GIS), interval Analytic Hierarchy Process (IAHP) and stochastic VIKOR was proposed to tackle site selection issue of wind farms in the Wafangdian region, China. Two major factors, i.e. biodiversity conservation and production safety, were utilized to determine feasible areas. Afterwards, the weight of evaluation criteria, including the social impact, economic benefit, terrain and eco-environment protection, were identified by using IAHP. Finally, the suitability indexes of various alternatives were calculated by stochastic VIKOR and their ranking was used to determine high-suitability areas for wind farm locations. The obtained results indicated that 30.2% of studied region were suitable for installing the wind-power facilities, but only 3.36% were determined to be highly suitable. By comparing the optimized results to the actual locations of existing wind farms, it was revealed that the ideological framework of this study were practical and effective in guiding site selection of wind farms, and they were also useful for applications in site selection of other renewable energy forms involving complex spatial analysis and multiple criteria evaluation, including solar, hydroelectric, geothermal and biomass. Highlights: A novel integrated method of IAHP and stochastic VIKOR was developed. A typical Chinese onshore wind farm site selection case was investigated. Social impact, economic benefit, terrain and eco-environment were considered. The suitability evaluation of candidate region for wind farm was conducted. Evaluated results shows 30.2% area favorable for wind farm arrangement.